2019
DOI: 10.1017/wet.2019.107
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide selection to terminate grass, legume, and brassica cover crop species

Abstract: Cover crops provide a number of agronomic benefits, including weed suppression, which is important as cases of herbicide resistance continue to rise. To effectively suppress weeds, high cover crop biomass is needed, which necessitates later termination timing. Cover crop termination is important to mitigate potential planting issues and prevent surviving cover crop competition with cash crops. Field studies were conducted in Virginia to determine the most effective herbicide options alone or combined with glyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…At 28 DAT, thifensulfuron + tribenuron and glyphosate provided 79 and 74% termination efficiency ( Table 6 ). Similar results were observed by Pittman et al, [ 22 ], where 80, 87, 81, and 69% termination efficiency at 28 DAT with 2,4-D, dicamba, glufosinate, and glyphosate was reported. All termination treatments reduced hairy vetch biomass 28 DAT.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…At 28 DAT, thifensulfuron + tribenuron and glyphosate provided 79 and 74% termination efficiency ( Table 6 ). Similar results were observed by Pittman et al, [ 22 ], where 80, 87, 81, and 69% termination efficiency at 28 DAT with 2,4-D, dicamba, glufosinate, and glyphosate was reported. All termination treatments reduced hairy vetch biomass 28 DAT.…”
Section: Resultssupporting
confidence: 90%
“…Thifensulfuron + tribenuron provided 43 and 51% termination 14 and 28 DAT. Askew et al, [ 21 ] and Pittman et al, [ 22 ] reported 34–70%, 9–40%, 50–67%, and 50–68% termination efficiency with 2,4-D, dicamba, glufosinate, and paraquat, respectively. Greater termination efficiency with paraquat in this study is attributed to greater spray volume used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cover crops are either damaged or killed by frost in winter (frost-sensitive cover crops) or actively desiccated by mowing, tillage, or application of chemical herbicides. The application of a non-selective herbicide (e.g., the active ingredient glyphosate) is a common method for desiccating cover crops because, compared with other desiccation methods, it can offer suitable levels of control at almost any time or plant growth stage [4][5][6]. However, a delay in desiccating the cover crop carries risks associated with the next crop emergence, such as water moisture depletion [3,7,8] and nitrogen immobilisation [8].…”
Section: Introductionmentioning
confidence: 99%